'Acolytes of history'?: Jazz music and nostalgia in Star Trek: The Next Generation. (February 2016) - Owen Jones, Craig
Abstract : A nostalgic scenario, experienced on the holodeck in an episode of Star Trek: The Next Generation, is analysed. It is proposed that certain narratological elements, including the diegetically unusual self-reflexivity of the scenario, prevent the protagonist from fully engaging with an environment – a simulacrum of a 1950s jazz bar – beyond his real-life experiences. The verisimilitude of the scenario and the implications of certain shortcomings in this regard for the nature of the beholder's experience are explored.